Sociodemographic and obstetric profile from pregnant women assisted in Iguatu - CE - Marcelo Luiz Carvalho Gonçalves (Revista Brasileira em Promoção da Saúde, 2012)
Objective: To evaluate the sociodemographic and obstetric profile of puerperae assisted in Iguatu-CE, Brazil. Methods: This is a descriptive study with quantitative approach. The sample consisted of 178 postpartum women living in the city under study. Data collectionwas conducted in a public maternity care in the city, from August to September 2008, through interviews. The data were analyzed by SPSS 11.0. The variables were subjected to univariate analysis. Results: The mean age was 23.8 years, 100 (56.2%) were from urban areas, 36(20.2%) were single, 109 (61.2%) of the household activities performed without pay, 110 (62.3%) began prenatal care in first quarter, 20 (11.2%) smoked and 6 (3.4%) drank alcoholduring pregnancy, 49 (28.2%) participated in some educational activity, 166 (96.6%) were VDRL the first and 108 (62.1%) had anti-HIV during prenatal. Conclusion: The sociodemographic profile of the studied population can be characterized by young puerperaewith some schooling, married or in stable relationships and family income between one and two minimum salaries, which made satisfactory amount of prenatal visits, had access to exams and had guarantee of delivery care in the public hospital of reference.